Differences in Lower Extremity Kinematics Between High School Cross-Country and Young Adult Recreational Runners - Mark F Reinking; Nina M Carson; Bridget M End; Olivia K Miller; Joshua D Munter; Thomas G McPoil (International Journal of Sports Physical Therapy)
# Background While previous research has assessed running kinematics for age-related differences that could increase the risk of a running-related injury, none of these studies have included high school aged runners or assessed running kinematics using 2-dimensional video analysis.